2002
DOI: 10.1046/j.1469-0691.2002.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive oral ganciclovir can reduce the risk of cytomegalovirus disease in liver transplant recipients

Abstract: A cohort of 65 liver transplant recipients was prospectively monitored with qualitative polymerase chain reaction (PCR) in plasma. The first 25 patients did not receive prophylaxis. From a consecutive group of 40 recipients, 11 high-risk patients donor CMV-seropositive/receptor CMV-seronegative (D+/R-), persistent CMV replication) received pre-emptive oral ganciclovir (1000 mg three times daily), when a marker of risk was identified, until day 90. The overall incidence of cytomegalovirus (CMV) disease at six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Subgroup analyses were performed on studies using each of these methods, and the analyses were compared to determine whether either method would significantly affect outcome data. [39][40][41][42][43][44][45][46][47] met the inclusion criteria for analysis (figure 1). One prospective head-to-head trial was identified that is not included in the meta-analysis, but it will be discussed later [13].…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Subgroup analyses were performed on studies using each of these methods, and the analyses were compared to determine whether either method would significantly affect outcome data. [39][40][41][42][43][44][45][46][47] met the inclusion criteria for analysis (figure 1). One prospective head-to-head trial was identified that is not included in the meta-analysis, but it will be discussed later [13].…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Preemptively administered oral ganciclovir at dosages ! 3 gm/day has also been shown to be effective in reducing the risk of CMV disease [20,30,31]. In liver transplant recipients, preemptive oral ganciclovir was associated …”
Section: Antiviral Agents For Preemptive Therapymentioning
confidence: 99%
“…Long-term use of valganciclovir as prophylaxis appears to pose a higher risk (5. [30]. Oral ganciclovir for 6 weeks initiated upon detectable CMV antigenemia was effective in preventing CMV disease in liver transplant recipients [20].…”
Section: Lowmentioning
confidence: 99%
“…CMV DNA in the follow-up of a liver recipients cohort, obtained SZ80%, EZ90%, PPVZ66% and NPVZ95%. 25 Similarly, Pellegrin et al when comparing pp65Ag with five molecular techniques for detection of CMV DNA in a cohort of renal allograft recipients, obtained even higher S (100 vs. 91%), E (61 vs. 47%), PPV (61 vs. 50%) and NPV (100 vs. 90%) of pp65Ag with respect to PCR. 20 Many of these authors conclude that techniques detecting CMV DNA could improve the results of pp65Ag, especially, when a delay in the sample processing occurs, due to the higher stability of CMV DNA compared with pp65Ag; 14,20 nevertheless, the handicap of PCR based molecular techniques rests on the difficulties in comparing the results obtained with different in-house developed PCR, thus many authors agree on the need of standardized methods in order to exactly assess the diagnostic value of molecular techniques.…”
Section: Discussionmentioning
confidence: 90%